Relative cost-effectiveness of using an extensively hydrolyzed casein formula in managing infants with cow’s milk allergy in Brazil - Guest JF; Yang AC; Oba J; Rodrigues M; Caetano R; Polster L (Dove Medical Press, 2016)
Julian F Guest,1,2 Ariana C Yang,3 Jane Oba,4 Maraci Rodrigues,5 Rosane Caetano,6 Lilian Polster7 1Catalyst Health Economics Consultants, Northwood, Middlesex, UK; 2Faculty of Life Sciences and Medicine, King’s College, London, UK; 3Universidade de São Paulo, São Paulo & Universidade Estadual de Campinas, São Paulo, Brazil; 4Hospital Israelita Albert Einstein, São Paulo, Brazil & Hospital Municipal Menino Jesus, São Paulo, Brazil; 5Department of Gastroenterology, University of São Paulo School of Medicine, São Paulo, Brazil; 6General Pediatrician, Rio de Janeiro, Brazil; 7General Pediatrician, São Paulo, Brazil Objective: To estimate the cost-effectiveness of three alternative dietetic strategies for cow’s milk allergy in Brazil: 1) using an extensively hydrolyzed casein formula (eHCF; Nutramigen) as a first-line formula, but switching to an amino acid formula (AAF) if infants remain symptomatic; 2) using an AAF as a first-line formula and then switching to an eHCF after 4 weeks once infants are symptom-free, but switching back to an AAF if infants become symptomatic; and 3) using an AAF as a first-line formula and keeping all infants on that formula. The analysis was conducted from the perspective of the Brazilian public health care system, Sistema Único de Saude.Methods: Decision modeling was used to estimate the probability of immunoglobulin E (IgE)-mediated and non-IgE-mediated allergic infants developing tolerance to cow’s milk by 12 months from starting a formula. The models also estimated the Sistema Único de Saude cost (at 2013/2014 prices) of managing infants over 12 months after starting a formula, as well as the relative cost-effectiveness of each of the dietetic strategies.Results: The probability of developing tolerance to cow’s milk by 12 months from starting a formula was higher among infants with either IgE-mediated or non-IgE-mediated allergy who were initially fed with an eHCF, compared with those who were initially fed with an AAF. The total health care cost of initially feeding an eHCF to cow’s milk allergic infants was less than that of initially feeding both IgE-mediated and non-IgE-mediated infants with an AAF.Conclusion: Within the study’s limitations, using an eHCF instead of an AAF for the first-line management of newly-diagnosed infants with cow’s milk allergy affords a cost-effective use of publicly funded resources, since it improves the outcome for less cost. Keywords: amino acid formula, Brazil, cost-effectiveness, cow’s milk allergy, extensively hydrolyzed formula